E-COMMERCE EMPOWERMENT: FUELING THE GROWTH AND PROSPERITY OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) IN THE DIGITAL AGE - S. Uplaonkar, Satish; Biradar, Sharanagouda S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Small businesses, often called MSMEs, are like the backbone of the world's economy. They create jobs and help economies grow. In recent years, the internet shopping revolution, known as e-commerce, has given small businesses an amazing chance to grow even more. This summary will look at how e-commerce helps small businesses become bigger and better. E-commerce has altered completely how people's business. It is like a tool that is low cost enabling small. As such, a few of these companies are able to quickly break into e-commerce simply by constructing a webpage for their stores. It does not only focus on earning money; it also focuses on innovations and building up new ideas. On top of that, e-commerce enables the functionality of small businesses to improve. It bolts up these businesses by providing organization of their inventories, reducing costs, and giving unique shopping experiences. Again, it employs smart tools to help entrepreneurs locate potential clients and interact with them further enhancing their loyalty. E-commerce relates small businesses and consumers across all corners of the world. Thus small businesses are able to stand a chance against the larger ones. It is also beneficial as it allows them to sell their products in foreign nations which creates more employment opportunities and develops the region. But, e-commerce isn't all sunshine and rainbows. Small businesses need to watch out for problems like online safety, moving stuff around, and learning how to use digital tools. Governments and businesses need to work together to help small businesses solve these issues. They should offer training, build the right stuff, and make rules that help, not hurt. E-commerce is like a magic potion for small businesses. It helps them reach more customers, save money, and go global. But, it's not magic – it needs help from everyone to make it work perfectly. When we do that, small businesses will grow even more, making more money, and giving more people good jobs.